(NmETODY OPTIMIZACII (B/s - (NhOMEN@K(B, (NwLADIMIR wLADIMIROWI^s; (NtRUHAEW(B, (Nr(B.(Ni(B.s; (NlENINGRADSKIJ GOSUDARSTWENNYJ UNIWERSITET IM(B. (Na(B.(Na(B. (NvDANOWAs ((NlENINGRAD (B:s (Nlgu(B,s, 1973)
(NsPISOK LIT(B.: (NS(B. 213-215s
Keywords: (NoPTIMALXNYE PROCESSYs